Comparison of Motivational Dimensions and Personality Traits in Medical Students of the School of Medicine and the International Campus of Iran University of Medical Sciences - Shahrzad Saravani; Hassan Mirzahosseini; Majid Zargham Hajebi (Zanjan University of Medical Sciences and Health Services, 2020)
Background & Objective Learning about and comparing personality traits and motivation in students enable us to understand negative biases for those who have different preferences. Therefore, this study aimed to compare the motivational dimensions and personality traits in students of the school of medicine and the international campus of Iran University of Medical Sciences, Tehran, Iran. Materials and Methods: This causal-comparative research was performed on all students studying basic medical sciences in Iran University of Medical Sciences in the academic year of 2017-2018. In total, 401 subjects were selected by stratified cluster sampling. Data were collected using Keller's motivation questionnaire and the NEO-Five Factor Inventory. In addition, data analysis was performed using MANOVA. Results According to the multivariate analysis results, there was no significant difference between the students of the school of medicine and the international campus in terms of personality traits and motivational dimensions (F(9&391)=1.33, P>0.05). Conclusion: According to the results of the present study, the school of medicine and the international campus of Iran University of Medical Sciences used similar medical student selection criteria, and the university has been able to create similar educational environments in the two mentioned places.